Fried sweetpotato user preferences identified in Nigeria and Ghana and implications for trait evaluation - Ssali, R.T.; Carey, E.E.; Imoro, S.; Low, Jan W.; Dery, E.; Boakye, A.; Oduro, I.; Omodamiro, R.M.; Yusuf, H.L.; Etwire, E.; Iyilade, A.; Adekambi, S.; et al. (Wiley, 2021)
Fried sweetpotato quality is important for variety adoption in West Africa. To inform breeding efforts, the study developed a product profile for sweetpotato chunk fries using mixed qualitative and quantitative methods. Root characteristics, processing attributes, in‐mouth attributes and appearance of fried product were critical to final product quality. Raw roots should be hard, have smooth skin and no off‐odours. Peeled roots should be hard to slice and not sticky. Stickiness and moist surface indicate high moisture content, associated with excessive oil absorption during frying. Hard to slice roots connote high dry matter. Fried product should be crisp, slightly sugary and mealy, have a uniform colour with brown tint and not be soggy. Crispness, mealiness and short frying time with limited oil absorption may be functions of starch. Understanding starch characteristics and other attributes that contribute to quality fried sweetpotato is critical for breeding sweetpotato genotypes with superior quality for frying.